Climate Change Effects on Fisheries and Crop Production in Bangladesh: An Econometric Analysis (South Asian Journal of Agriculture, 2025)
This research paper presents an econometric analysis of the effect of climate change on fisheries and crop production in Bangladesh, as well as the associated economic losses. The study utilizes annual time series data from 1971 to 2020 and employs various econometric tests. The results reveal that average rainfall, minimum temperatures, and greenhouse gas emissions positively influence fisheries and the production of crops like rice, potato, and jute. Sufficient rainfall and warmer minimum temperatures play a role in boosting fishery and crop yields, while the release of greenhouse gases enhances the rates of photosynthesis and water use efficiency, leading to increased production. Conversely, floods, high temperatures, and changes in arable land area have adverse effects on fisheries and crop production. Floods submerge crops, disrupt fish migration and spawning, and damage fish farms and ponds. Infrastructural development and residential construction negatively affect on fisheries and crop production. The increase in maximum temperature leads to water scarcity and intense weather events, further impacting fish and crop production. Climate change-induced floods cause significant financial losses for farmers, while higher temperatures escalate pest control expenses and alter rainfall patterns, impacting profitability and fish populations. It results in a decline in crop yields, affecting daily wages and consumption, and increasing the financial burden on small-scale farmers. Climate change consistently affects Bangladesh's GDP, will pose harm to agricultural net trade from 2020 to 2050.The fisheries and crop sectors have experienced substantial financial losses over the past decade due to climate change. The study shows that the urgency for preventative action and policy interventions to mitigate the adverse effects of climate change, safeguard livelihoods, ensure food security, and promote sustainable economic development of Bangladesh.South Asian J. Agric., Vol. 10, No.1-2, 2024: 11-23